The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21873/anticanres.15291
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-thrombotic Efficacy of Targeted Ultrasound Microbubbles on LPS-induced HUVEC Cells

Abstract: Materials and MethodsLigand conjugation of microbubbles. One vial (800 μL) of streptavidin-labeled ultrasound microbubbles (MBs) USphere™ Labeler-LS (TRUST Bio-sonics, Zhubei, Taiwan, ROC) was 4761 This article is freely accessible online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…An increased expression of ET-1 receptors has been found in inflammatory cells (macrophages, T lymphocytes) and in the smooth muscle fibers of the vessels. It has been suggested that foam cells and T-lymphocytes regulate a switch in expression from ETA to ETB-receptors in vascular endothelial smooth muscle fibers [45]. However, only in vitro data have reported that bosentan has the potential of suppressing inflammation through the modification of inflammatory agents like TNF-a and MCP-1 in models simulating atherosclerosis [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…An increased expression of ET-1 receptors has been found in inflammatory cells (macrophages, T lymphocytes) and in the smooth muscle fibers of the vessels. It has been suggested that foam cells and T-lymphocytes regulate a switch in expression from ETA to ETB-receptors in vascular endothelial smooth muscle fibers [45]. However, only in vitro data have reported that bosentan has the potential of suppressing inflammation through the modification of inflammatory agents like TNF-a and MCP-1 in models simulating atherosclerosis [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…An increased expression of ET-1 receptors has been found in inflammatory cells (macrophages, T lymphocytes) and in the smooth muscle fibers of the vessels. It has been suggested that foam cells and T-lymphocytes regulate a switch in expression from ET A to ET B receptors in vascular endothelial smooth muscle fibers [ 48 ]. However, only in vitro data have reported that bosentan has the potential of suppressing inflammation through the modification of inflammatory agents like TNF-a and MCP-1 in models simulating atherosclerosis [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%